2019
DOI: 10.1097/cm9.0000000000000127
|View full text |Cite
|
Sign up to set email alerts
|

Matrine suppresses lipopolysaccharide-induced fibrosis in human peritoneal mesothelial cells by inhibiting the epithelial-mesenchymal transition

Abstract: Background:Peritoneal fibrosis is the primary reason that patients with end-stage renal disease (ESRD) have to cease peritoneal dialysis. Peritonitis caused by Gram-negative bacteria such as Escherichia coli (E. coli) were on the rise. We had previously shown that matrine inhibited the formation of biofilm by E. coli. However, the role of matrine on the epithelial-mesenchymal transition (EMT) in peritoneal mesothelial cells under chronic inflammatory conditions is still unknown.Methods:We cultured human perito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…FN is a noncollagenous glycoprotein with important biological Previous research indicated that FN is upregulated in PF, promoting epithelial-mesenchymal (EMT) in peritoneal mesothelial cells. 21 Our findings show a significant increase in FN expression in patients with more than 5 years of dialysis (p < 0.05), consistent with previous reports. Moreover, there was a positive correlation between IGF2BP3 and FN (r = 0.340, p = 0.030), further indicating a close relationship between IGF2BP3 and PF.…”
Section: Discussionsupporting
confidence: 93%
“…FN is a noncollagenous glycoprotein with important biological Previous research indicated that FN is upregulated in PF, promoting epithelial-mesenchymal (EMT) in peritoneal mesothelial cells. 21 Our findings show a significant increase in FN expression in patients with more than 5 years of dialysis (p < 0.05), consistent with previous reports. Moreover, there was a positive correlation between IGF2BP3 and FN (r = 0.340, p = 0.030), further indicating a close relationship between IGF2BP3 and PF.…”
Section: Discussionsupporting
confidence: 93%
“…The epithelial-to-mesenchymal transition (EMT) is a biological process strongly associated with tumor progression, invasion, and metastasis ( 39 , 40 ). As the concentration of BCAA increased in the culture medium, the expression of N-Cadherin, a key mesenchymal marker, dramatically decreased in LM2 cells ( Figure 6G ).…”
Section: Resultsmentioning
confidence: 99%
“…, matrine has antibacterial, anti-inflammatory, antitumor, and antiarrhythmia effects. Matrine has an inhibitory effect on the inflammatory reactions caused by liposaccharides (LPS) [ 23 , 24 ] LPS, a component of the cell wall of gram-negative bacteria, acts on the Toll-like receptors 4 (TLR4) receptor to induce myeloid differentiation factor88 (MyD88) recruitment, followed by activation of nuclear factor kappa-B (NF- κ B) through a series of phosphorylation cascades [ 25 ]. After the inflammatory factors destroy the blood-aqueous barrier or blood-retinal barrier, some macromolecular protein substances and cells in the blood infiltrate into the interstitial or intracavity of the eye (anterior chamber or vitreous body), giving rise to different degrees of tissue damage [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Extracted from the dried root of Sophora flavescens, Alt., matrine has antibacterial, anti-inflammatory, antitumor, and antiarrhythmia effects. Matrine has a good inhibitory effect on the inflammatory reaction caused by LPS [17,18]. Liposaccharides (LPS), a component of the cell wall of gram-negative bacteria, acts on the TLR4 receptor to induce MyD88 recruitment, followed by activation of NF-κB through a series of phosphorylation cascades [19].…”
Section: Alkaloidsmentioning
confidence: 99%